2003
DOI: 10.1210/jc.2003-030515
|View full text |Cite
|
Sign up to set email alerts
|

Low Vitamin D Status, High Bone Turnover, and Bone Fractures in Centenarians

Abstract: The oldest olds, including centenarians, are increasing worldwide and, in the near future, will represent a consistent part of the population. We have studied bone status and metabolism in 104 subjects over 98 yr of age to evaluate possible interventions able to avoid fragility fractures and disability. Ninety females and 14 males not affected by any acute disease were considered. After a complete clinical assessment, blood was drawn for evaluating bone turnover markers, and performance tests together with ske… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
65
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(68 citation statements)
references
References 54 publications
2
65
1
Order By: Relevance
“…In our study, the correlation between OPG and bone resorption was found in the old subjects who were under 85 years of age but not in the long-lived subjects. This finding was really unexpected, since several studies had already demonstrated that in the presence of osteoporosis, as found in long-lived subjects (25), serum OPG values should be strictly correlated with bone turnover (13 -16). Although we did not evaluate the bone structure in our subjects, the huge increase in serum bone resorption markers in long-lived subjects would suggest that the bone was impaired in this population, in agreement with previous observations (25).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In our study, the correlation between OPG and bone resorption was found in the old subjects who were under 85 years of age but not in the long-lived subjects. This finding was really unexpected, since several studies had already demonstrated that in the presence of osteoporosis, as found in long-lived subjects (25), serum OPG values should be strictly correlated with bone turnover (13 -16). Although we did not evaluate the bone structure in our subjects, the huge increase in serum bone resorption markers in long-lived subjects would suggest that the bone was impaired in this population, in agreement with previous observations (25).…”
Section: Discussionmentioning
confidence: 95%
“…This finding was really unexpected, since several studies had already demonstrated that in the presence of osteoporosis, as found in long-lived subjects (25), serum OPG values should be strictly correlated with bone turnover (13 -16). Although we did not evaluate the bone structure in our subjects, the huge increase in serum bone resorption markers in long-lived subjects would suggest that the bone was impaired in this population, in agreement with previous observations (25). Another interesting finding was the disappearance of a correlation between OPG and RANKL in long-lived subjects when the statistical analysis was performed by the multivariate instead of the univariate approach.…”
Section: Discussionmentioning
confidence: 95%
“…In addition, correlations were found between PTH and calcium (r = −0.33, p < 0.001), IL-6 and S-CTX (r = 0.37, p < 0.001), IL-6 and calcium (r = −0.35, p < 0.001), PTH and IL-6 (r = 0.24, p = 0.019). There was no correlation between the creatinine clearance and PTH (r = −0.167, p = not significant) (Passeri et al, 2003).…”
Section: Bone Metabolism In Centenariansmentioning
confidence: 89%
“…There was also a significant correlation between markers of bone turnover and ultrasonographic parameters both at the phalanges and at the calcaneous: PTH and S-CTX versus phalangeal UBPI (r = −0.38, p = 0.032; r = −0.28, p = 0.036, respectively), S-CTX versus calcaneal SoS (r = −0.4, p = 0.05) (Passeri et al, 2003). …”
Section: Bone Metabolism In Centenariansmentioning
confidence: 91%
“…In addition, their skin exposure to the solar ultraviolet B spectrum is often limited owing to a sedentary lifestyle or complete institutionalization. In line with these considerations, more than 95% of a cohort of centenarians had undectable 25(OH)D levels [6]. Interestingly, an anecdotal report of one of the oldest men who ever lived, a Ukrainian who recently died at the age of almost 120 years, informs us that this man ate herring, one of the very few vitamin D-rich foods, several times a week.…”
Section: For Reprint Orders Please Contact: Reprints@futuremedicinecommentioning
confidence: 93%